Multiple Orbital Angular Momentum Beams with High‐Purity of Transmission‐Coding Metasurface. Issue 4 (15th February 2023) - Liu, Xiaobin; Li, Sijia; He, Chengyuan; Li, Zhuoyue; Huang, Guoshuai; Cao, Xiangyu
Abstract: Vortex electromagnetic wave carrying orbital angular momentum (OAM) is expected to break through the shortage of spectrum resource because of its multiple independent modes. Nowadays, there are various methods to generate OAM vortex beam. Based on the concepts of digital metasurface and propagation phase, a broadband 3‐bit coding transmission metasurface is designed and illustrated by simulation and measurement. The elements exhibit the different phase by changing the size of metal patch, and the focusing phase is introduced to reduce the divergence of OAM beams. Based on the principle of phase superposition, the wide‐band, high‐purity, and multi‐beam OAM vortex waves can be generated by the transmission‐coding metasurface (TCMS). The experimental results verify that TCMS realizes the multiple OAM beams along different directions simultaneously from 9 to 10.5 GHz, which are consistent with the theoretical results. The high purity more than 90% of OAM mode is demonstrated by both the simulated and measured results. The TCMS provides a potential and effective scheme for OAM multiplexing and multi‐target positioning in wireless systems. Abstract : A broadband 3‐bit coding transmission metasurface is designed based on the concept of digital metasurface and propagation phase. The wide‐band, high‐purity, and multi‐beam orbital angular momentum (OAM) vortex waves can be generated by the transmission‐coding metasurface (TCMS) with the phase superposition. The TCMS provides a potential and effective scheme for OAM multiplexing and multi‐target positioning in wireless systems.